Cultural Heritage and Mediation: The Use of ICT in the Communication of the Artistic Layers of the Church of Saint John the Baptist of Foz do Douro - Cruz, Tiago; Pereira Santos, Marisa (Mimesis Journal, 2024)
In the contemporary era, digital media is pivotal for researching, disseminating and promoting Cultural Heritage within communities. This article, centered on the Parish Church of Saint John the Baptist of Foz do Douro, highlights the value of employing 3D reconstruction and a 360º virtual tour for effectively communicating and promoting local heritage. Capitalizing technological advancements, these tools enhance understanding of the specificities and historical importance of built heritage, fostering bilateral relations between civil society and their collective Cultural Heritage.